Predicting organizational commitment through organization culture: A study of automobile industry in India - Singh, Kavita (Journal of Business Economics and Management, 2007)
The extent to which the employees of an organization feel committed to their organization can be easily gathered from the strength of its culture. This points out that even though the culture is holistic, it can be strengthened by commitment. Culture can be managed by managing the employees of the organization and also by leader’s actions and interventions and these are also understood as the targets of management of commitment. Management of commitment is also the management of culture, as it is commitment that binds people to organization’s ideas and agents. With these notions in mind, the present study makes an attempt, firstly, to integrate different conceptual constructs of commitment and culture and secondly, to identify the relationship between organizational commitment and organization culture. The study is based on a sample of 382 executives from five automobile companies. The findings indicate that most of the dimensions of organizational culture are positively and significantly related to the dimensions of organizational commitment. Some of the dimensions of culture also made significant contribution to predict organizational commitment. The main issue that emerges from this study is that the importance of organizational culture in understanding organizational commitment can neither be underestimated nor overlooked. First Published Online: 14 Oct 2010